Mídias sociais na web: uma análise da mídia De olho na CI na perspectiva da disseminação da informação. - Lima, Aline Poggi Lins de (2013)
This research addresses the De olho na CI in the perspective of the following social media: Internet - Blog, Twitter and Facebook - viewed as resources capable of developing Social Networks on the Internet (SNI), and as a means of information dissemination. Its main aim was to analyze how the dissemination of interest for information professionals occurs through the social media De olho na CI. It adopts the reference of being a descriptive research, of qualitative approach, using part of the methods of virtual ethnography, participant observation and field diary for data collection. Data were analyzed from the perspective of documental analysis, linked to the context of web search, joining the Social Network Analysis in order to achieve the objectives proposed in the research. It was concluded, during the research, that the social media De olho na CI enable the occurrence of social networks on the internet and that they showed significant growth between the internet network and the information professionals seeking knowledge for their professional training.